A Dissertation Report on Security System using GSM - RAMESH BABU N (2003)
INTERNAL GUIDE: M PAULINE M E, MVJCE EXTERNAL GUIDE: GIRIDHAR K L, SENIOR SOFTWARE ENGINEER, CITL
Keywords: Security System using GSM